DNA methylation directs genomic localization of Mbd2 and Mbd3 in embryonic stem cells - Hainer, Sarah J; McCannell, Kurtis N; Yu, Jun; Ee, Ly-Sha; Zhu, Lihua J; Rando, Oliver J; Fazzio, Thomas G (eLife, 2016)
Cytosine methylation is an epigenetic and regulatory mark that functions in part through recruitment of chromatin remodeling complexes containing methyl-CpG binding domain (MBD) proteins. Two MBD proteins, Mbd2 and Mbd3, were previously shown to bind methylated or hydroxymethylated DNA, respectively; however, both of these findings have been disputed. Here, we investigated this controversy using experimental approaches and re-analysis of published data and find no evidence for methylation-independent functions of Mbd2 or Mbd3. We show that chromatin localization of Mbd2 and Mbd3 is highly overlapping and, unexpectedly, we find Mbd2 and Mbd3 are interdependent for chromatin association. Further investigation reveals that both proteins are required for normal levels of cytosine methylation and hydroxymethylation in murine embryonic stem cells. Furthermore, Mbd2 and Mbd3 regulate overlapping sets of genes that are also regulated by DNA methylation/hydroxymethylation factors. These findings reveal an interdependent regulatory mechanism mediated by the DNA methylation machinery and its readers.
Keywords: DNA methylation; DNA hydroxymethylation; NuRD; chromatin; nucleosome; embryonic stem cells